Do BL Lacs lack the circular polarization? - Podorvanyuk, N.Yu.; Vitrishchak, V.M.; Pashchenko, I.N.; Gabuzda, D.C. (Advances in Astronomy and Space Physics, 2011)
We present the first preliminary evidence of difference in the circular polarized emission between quasars and BL Lacs. BL Lac objects seem to lack the sources with high circular polarization degrees. It cannot be due to selection effects, so some intrinsic effects are involved. These possible differences can be attributed to jet composition, energy of particles or magnetic field properties. The first one can be the intriguing possibility of different central engine mechanisms of these objects. However, the small detection rate for BL Lac objects and therefore a small sample size still prevents us from making the firm conclusion, so further observations of BL Lacs are highly desired.